Kewajiban Pemenuhan Hak Konstitusional Teman Tuli dalam Mengakses Informasi di Mahkamah Konstitusi - Rima Yuwana Yustikaningrum (Jurnal Konstitusi, 2020)
As one of the judiciary bodies in Indonesia, which plays a role as the human right protector, the Constitutional Court have a significant part to ensure the fulfilment of the Indonesians’ human right. Moreover, before signing the Convention on the Rights of Persons with Disabilities in 2007 in New York and ratifying it in 2011, Indonesia had recognized human rights under its constitution, namely UUD 1945. Furthermore, the government of Republic Indonesia has been approving Act number 8 the Year 2016 about Persons with Disabilities in 2016. Under this act, the deaf has its recognized rights, especially to access information, to choose the preferable kind communication forms as it needs, and the affirmation of the state’s obligations to fulfil their human rights equally. However, the Constitutional Court has yet to have a standard operating procedure yet which specifically regulates the mechanism of accessible information for the deaf. Accordingly, in disseminating information to the public, not all people can access the information. In other words, the deaf find difficulties to comprehend the content of the message conveyed by the Court to the public as the Court do not consistently provide any tools, such as sign language interpreter and written texts. Thus, it is safe to submit that accessible information is yet to be provided by the Court in terms of publishing the information to the public. This article discusses the obligation of the Constitutional Court to ensure the fulfillment of the deaf right to access information. The aim of elaborating some related cases law and an applied standard operational procedure in Georgia’s Court in this article is that to remind the Constitutional Court to be consistent in ensuring the enjoyment and fulfillment of the deaf right to access information as the constitution recognize equality for all.